2000
DOI: 10.1144/gsl.sp.2000.179.01.18
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical constraints on exhumation mechanisms of high-pressure rocks: the Saxo-Thuringian case between the Franconian Line and Elbe Zone

Abstract: Major bodies of high-pressure (HP) rocks in the Saxo-Thuringian Belt in East Germany (Saxonian Granulite Massif, Erzgebirge) are investigated using a variety of geophysical methods (seismic reflection and refraction survey, magnetotelluric studies, gravity modelling). The Saxonian Granulite Massif and the Erzgebirge are not a continuous feature, as can be seen from discontinuous reflections, offset of upper-crustal seismic refraction velocity layers, and crustal resistivity increasing towards the Erzgebirge. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The Rhenohercynian lithosphere was subducted under the Saxothuringicum, which was in turn overthrust by the rocks of the Moldanubian zone. The subductions were active in Late Devonian to Carboniferous time (Krawczyk et al, 2000). Franke (1989) classified the Teplá-Barranian unit as a part of the Moldanubian zone.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Rhenohercynian lithosphere was subducted under the Saxothuringicum, which was in turn overthrust by the rocks of the Moldanubian zone. The subductions were active in Late Devonian to Carboniferous time (Krawczyk et al, 2000). Franke (1989) classified the Teplá-Barranian unit as a part of the Moldanubian zone.…”
Section: Geological Settingmentioning
confidence: 99%
“…It has been investigated by several refraction and reflection profiles (e.g., Trappe and Wever, 1990;DEKORP, 1994;Krawczyk et al, 2000;Hrubcová et al, 2005;Grad et al, 2008) which imaged a highly reflective, about 4-6 km thick, lowermost crust of the ST. Reflection profile 9HR of Tomek et al (1997) showed a distinct inclined underthrusting of the ST crust beneath the TB.…”
Section: Lithosphere Architecture and Locations Of Volcanic Phenomenamentioning
confidence: 99%
“…The first phase can be correlated to the development of the Saxo-Thuringian belt marked by two successive thrust events. The first occurred during the Saxo-Thuringian-Tepla-Barrandian collision (340-320 Ma) and the second during the Saxo-ThuringianRheno-Hercynian collision that ended at c. 310 Ma (Krawczyk et al 2000). We could with advantage refer, following Cavazza et al 2004, to (1) with the collisional climax between the Hunic and Hanseatic terranes with Laurussia at c. 340 Ma followed by a period of lateral displacement accompanied by major plutonism and (2) an Alleghenian orogeny with the collisional climax between Gondwana and Laurentia at c. 300 Ma, also followed by an important magmatic event attaining the Early Permian.…”
Section: Geodynamical Settingmentioning
confidence: 99%